The social responsibility of universities through the prism of cinematic memory - María José Chisvert Tarazona (Universitat Politècnica de València, 2013)
This article reviews 'Educating Rita', an interesting British film shot in 1983 by Lewis Gilbert. The film offers a faithful depiction of the beginnings of the Open University, a pioneer in university-level distance learning in Europe thanks to its innovative educational spirit. The film explores relevant issues at the core of higher education, analyzing them in at least four dimensions: the culture of the educational institution, teachers' professionalism, teaching methodology and the role of students in higher education. A facilitating element and theme for curricular reflection underlying these four dimensions is the orientation of university curricula. An interest in questioning the meaning of universities is linked to the recovery of the notion of academic mission. These are closely connected to the notion of intellectual excellence and to the scientific development underlying three main activities: research, teaching and outreach. All three addressed the university mission to generate and disseminate knowledge and culture. University outreach aims to strengthen the links between higher education institutions and their social surroundings, as an expression of social responsibility within the university. However, outreach lacks sufficient acknowledgment as a privileged function. For this reason, it is often left aside in recent curricula developed by the European Higher Education Area, where only specific entry tests for adult learners are offered. Late transitions into university requires new curriculum proposals if they are intended to integrate adult learners.